Development of Learning Materials Based on Local Culture in Basic School Using Waterfall Methods - Ragalutu, Herlina; Ibrahim, Nurdin; Nomida, Diana (International Journal of Psychosocial Rehabilitation, 2020)
Development of Learning Materials is a process that will be carried out on devices that will be used in the learning process. Education is rooted in national culture and regional culture as a pillar of national culture. This study aims to produce local culture-based learning material in Class IV Elementary School (SD). Local culture is a habit that grows and develops and is owned and recognized by local tribal communities. This culture will later be used as the basis for developing learning materials. The steps for developing teaching materials follow the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with the Research and Development method. The product of development research is the Nosarara Nosabatutu Module with expert validity test results. The Waterfall method is a model that is often called the classic life cycle, which describes a systematic and sequential approach to software development that can be implemented in various developments. The results showed that the module-shaped learning material nosarara nosabatutu is suitable for use in elementary school learning in Palu City as evidenced by the results of language expert validation of 3.9 (good), design experts validation of 4,3 (very good), mater expert validation of 4.5 (very good), teacher validation of 4.5 (very good). This data is reinforced by the validation of the readability of one to one learners by 86.8%, the effectiveness of learning materials through completeness testing in small groups with 100% classical completion results and an increase in the learning outcomes of pretest and posttest by 81.08% (criteria sufficient 29.73% ; good criteria 32.43%; very good criteria 18, 92%). Nosarara nosabatutu module-shaped learning material has been integrated with a communication technology-based learning system by including barcodes from online learning sources that can be operated with QR Scanner Nosarara Nosabatutu (QR. NN Scanner).